2019
DOI: 10.3390/en13010080
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Payback of Renovation Strategies in a Northern Climate—the Impact of Nuclear Power and Fossil Fuels in the Electricity Supply

Abstract: The aim of this study is to assess how the use of fossil and nuclear power in different renovation scenarios affects the environmental impacts of a multi-family dwelling in Sweden, and how changes in the electricity production with different energy carriers affect the environmental impact. In line with the Paris Agreement, the European Union has set an agenda to reduce greenhouse gas emissions by means of energy efficiency in buildings. It is estimated that by the year 2050, 80% of Europe’s population will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The emission factor for the Nordic mix is currently around 90 g/kWh [62], whereas in the EU, the emission factor for electricity was 334 g/kWh in 2019 [68]. Utilizing this factor in the life cycle assessment can significantly impact this study's results, as demonstrated in a former study conducted by Ramirez [40]. It is important to emphasize that, both today and in all future electricity scenarios, Sweden is a net exporter of electricity [43].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The emission factor for the Nordic mix is currently around 90 g/kWh [62], whereas in the EU, the emission factor for electricity was 334 g/kWh in 2019 [68]. Utilizing this factor in the life cycle assessment can significantly impact this study's results, as demonstrated in a former study conducted by Ramirez [40]. It is important to emphasize that, both today and in all future electricity scenarios, Sweden is a net exporter of electricity [43].…”
Section: Discussionmentioning
confidence: 95%
“…To offer insights into the environmental impact of building materials, the software incorporates predictions of CO 2 e emissions using EPD datasets available within the tool. One Click LCA has been employed in various studies to evaluate the environmental impact of diverse projects [40,41,[53][54][55].…”
Section: Life Cycle Analysis (Lca)mentioning
confidence: 99%
See 1 more Smart Citation
“…cradle to grave) GHG emissions of HPC, using the three main LCA methods and publicly available information that is relevant to the plant or the wider context. In addition to the contribution that our work makes to the literature on nuclear energy, it is useful to note that the carbon-intensity of nuclear energy, is also used as input data in other studies, for instance in investigating future scenarios for building renovations [12], thus enhancing the importance of reliable and accurate numbers.…”
Section: The Uk Contextmentioning
confidence: 99%
“…Nevertheless, the projected spike in supply and use of energy presents a serious challenge for the global community regarding the sustainability of our energy system (Khaled et al 2017;Blomqvist et al 2019). This makes it imperative to modify the supply and use patterns, to avert irreversibly harmful effects on the climate and environment (Ramírez-Villegas et al 2020). There are several possibilities to realizing such an objective.…”
Section: The Sustainable Development Goals and Energymentioning
confidence: 99%